Allelic diversity of the Vrn genes and the control of growth habit and earliness in wheat - S. E. Smolenskaya; N. P. Goncharov (Вавиловский журнал генетики и селекции)
Wheat is one of three main food crops around the world, which has the largest distribution area due to its adaptation to the different environments. This review considers polymorphisms and allelic variation of the vernalization response genes Vrn controlling the major adaptation traits in wheats (the genus Triticum L.): growth habit (spring vs. winter) and length of vegetative period (earliness). The review summarizes available information on the allelic diversity of the Vrn genes and discusses molecular-level relationships between Vrn polymorphisms and their effect on growth habit (spring vs. winter) and earliness (length vegetative period in spring plants) in di-, tetra- and hexaploid wheat species. A unique attempt has been made to relate information on mutations (polymorphisms) in dominant Vrn alleles to the values of the commercially most important trait “length of plant vegetative period (earliness)”. The effects of mutations (polymorphisms) in the recessive vrn genes on vernalization requirement in winter wheats are considered, and this trait was formalized. The evolution of the winter/spring growth habit in the genus Triticum  species is discussed. A scheme of phylogenetic interactions between Vrn alleles was constructed on the basis of these polymorphisms; the paper considers the possibilities to enhance the diversity of polymorphisms for the dominant Vrn genes and their alleles using wheat related species and rarely used alleles and discusses the prospects of breeding for improved earliness for concrete agroecological zones.